Real-Time Fuzzy Logic Control of Switched Reluctance Motor - Uysal, Ali (International Journal of Intelligent Systems and Applications in Engineering, 2017)
In this study, 8/6 switched reluctance motor (SRM) is controlled by fuzzy logic. For driving SRM, four phase asymmetric bridge converter is chosen. STM32F4 Discovery processor and MATLAB Simulink software fuzzy logic controller (FLC) are used. SRMâs speed and current are transferred to the computer in real-time. Measured speeds and currents are plotted. It is shown here that, the SRM for different reference speeds and loads is controlled by a STM32F4 Discovery card with MATLAB Simulink FLC.